Shake table tests and numerical investigation of a resilient damping device for seismic response control of building structures - Bogdanovic, A. and Rakicevic, Z. and Noroozinejad Farsangi, E. (My University, 2019)
In this study, shake table tests of a multistory steel frame structure designed according to Eurocodes 3 and 8 with and without the newly developed prestressed viscous damper (PVD) have been carried out at the Institute of Earthquake Engineering and Engineering Seismology in Macedonia. An array of strong ground motion records has been applied to the reduced-scale test structure to assess the efficiency and seismic performance of the equipped building with PVDs. It has been revealed that with the implementation of this system, the structural responses were suppressed in the range of 10% to 70%. Series of sensitivity analyses have been performed within the study to investigate the effect of the individual parameters and evaluate the effectiveness of the proposed system. Besides the experimental investigations, extensive numerical simulations of the structure without PVDs versus structure with three different damper placements were performed in ANSYS nonlinear platform, and part of the results that are presented in this paper confirms the remarkable structural performance improvement when using this system. The results also exhibit that the developed finite element models are properly verified through the experimental results and have the capabilities to further investigate the proposed system. It is likely that the proposed control strategy can be used for practical implementations into full-scale buildings to improve the urban seismic resilience.
Keywords: damper placement, numerical modeling, prestressed viscous damper, seismic resilience, shake table test, vibration control